Thunderstorm climatology over Indian region - TYAGI, AJIT (MAUSAM, 2007)
Thunderstorm is a severe weather phenomenon, the impact of which is being increasingly felt by all the sectors of society. In this study attempt has been made to develop thunderstorm climatology over Indian region based on latest representative climatological data. In all, data of 450 observatories comprising of 390 IMD observatories, 50 IAF observatories, six Bangladesh observatories, two Pakistan observatories, and one each in Nepal and Sri Lanka have been analysed. Inclusion of climatological data of Indian Air Force and Bangladesh has helped in developing representative climatology over Indian region. The study has brought out higher (100-120 days) annual frequency of thunderstorm as compared to those given by earlier studies (80-100 days). The highest annual frequency (100-120 days) is observed over Assam and Sub Himalayan West Bengal in the east and Jammu region in the north. The lowest frequency (less than 5 days) is observed over Ladakh region. In the plains Gangetic West Bengal and Bangladesh record between 80 and 100 days of thunderstorm annually. Kerala records highest (80-100 days) thunderstorm frequency of thunderstorm over peninsula. Udhampur observatory (132 days) in Jammu sub-division records highest number of thunderstorms in the country followed by Kumbhigram (Silchar) observatory (129 days) in south Assam and Hasimara (123 days) in Sub Himalayan West Bengal. In the plains Saurashtra and Kutch record lowest number (less than 15 days) of thunderstorm in the country. Thunderstorms are primarily short lived mesoscale weather phenomena. Existing synoptic network of part time observatories have limitations in recording all the occurrences of thunderstorms at the observatory and adjoining areas. Inclusion of data from such observatories results in lower frequency of the event and vitiates climatology. Efforts have been made in this study to develop thunderstorm climatology by using quality data of full time current weather (Airport) observatories, class I and selected class II IMD observatories. Since number of full time observatories in most of the sub divisions is few, the study is not able to bring out finer spatial variation of thunderstorm activity with in sub-divisions. Thunderstorm is a high impact severe weather event, which affects all the sectors of the society. Therefore, both from operational and climatological point of view, there is urgent need to establish at least one full time current weather observatory in each district to ensure proper reporting of all thunderstorm occurrences and to build district level thunderstorm climatology in the country.